“Smart-Bung” Media Belajar Teknik Dasar Bulutangkis Berbasis Android: inggris & indonesia - Debian Solekhudin; Ibnu Fatkhu Royana (Journal of Physical Activity and Sports (JPAS), 2022)
Abstract "Development of Android-Based Badminton Basic Technique Learning Media" SMART-BUNG "at SMKN 9 Semarang". Health and Recreation Physical Education Study Program. Faculty of Social Sciences and Sports Education. PGRI University in Semarang. 2020. This research is motivated by the lack of interesting learning media innovations that exist for learning PJOK, especially about basic badminton techniques and the difficulty of some students in understanding the basic badminton techniques taught in schools due to the lack of student interest in learning PJOK, especially badminton when in class or learning theory. . This study aims to develop a learning application for the basic techniques of badminton "smart-bung" for high school / vocational high school students around the world. This research is a research development or Research and Development (R&D) which uses the ADDIE development model. There are 5 stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation, Product validation is carried out by material experts and experts. media. Media. then developed and tested the feasibility of the product to the teacher and 106 students of class XI AKL SMKN 9 Semarang. The results of the descriptive analysis of the percentage of data showed that the questionnaire of material experts and instructional media experts was 83% with the category "suitable for use without revision". The results of the teacher response questionnaire analysis were 89% with the category "very feasible to use". The results of the student response questionnaire analysis were 94% with the category "very feasible to use". . Keywords: Development, Basic Badminton Techniques, smart-bung, android Abstrak “Pengembangan Media Pembelajaran Teknik Dasar Bulutangkis Berbasis Android “ SMART-BUNG” di SMKN 9 Semarang”. Program Studi Pendidikan Jasmani Kesehatan Dan Rekreasi. Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Keolahragaan. Universitas PGRI Semarang. 2020. Penelitian ini dilatar belakangi oleh kurangnya inovasi media pembelajaran yang menarik yang ada untuk pembelajaran PJOK khususnya tentang teknik dasar bulutangkis dan kesulitan beberapa siswa dalam memahami teknik dasar bulutangkis yang diajarkan di sekolah karena kurangnya minat belajar siswa dalam pembelajaran PJOK khususnya bulutangkis ketika di kelas atau pembelajaran teori. Penelitian ini memiliki tujuan untuk mengembangkan aplikasi pembelajaran teknik dasar bulutangkis “smart-bung” untuk siswa SMA/SMK se-drajat. Penelitian ini merupakan penelitian pengembangan atau Research and Development (R&D) yang menggunakan model pengembangan ADDIE. Tahapannya ada 5 tahap yaitu: 1) Analysis (Analisis), 2) Design (Perancangan), 3) Development (Pengembangan), 4) Implementation (Implementasi), dan 5) Evaluation (Evaluasi), Validasi produk dilakukan oleh ahli materi dan ahli media. Media. kemudian dikembangkan dan diuji cobakan kelayakan produk kepada Guru dan 106 siswa kelas XI AKL SMKN 9 Semarang. Hasil analisis melalu Deskriftif presentase data menunjukkan bahwa angket ahli materi dan ahli media pembelajaran adalah 83% dengan kategori “ layak digunakan tanpa revisi”. Hasil analisis angket respon guru adalah 89% dengan kategori “sangat layak digunakan”. Hasil analisi angket respon siswa adalah 94% dengan ketegori “sangat layak digunakan”. . Kata kunci: Pengembangan, Teknik Dasar Bulutangkis, smart-bung, android